Thailand Economic Monitor, June 2016 : Aging Society and Economy - Ariyapruchya, Kiatipong (World Bank, Bangkok, 2016)
The Thai economy shows signs of a nascent recovery but faces challenges on the path toward a broad-based and sustained recovery. The Thai economy accelerated to 2.8 percent in 2015, compared to 0.9 percent in 2014, partly on the basis of government consumption and investment, and partly on declining imports. Tourism and private consumption have mildly recovered, whereas merchandise exports dropped in the last quarter of 2015. Economic growth is expected to moderate to 2.5 percent in 2016 primarily due to sluggish exports of goods and private investment amid a slowing and difficult global environment. Fiscal stimulus and tourism receipts will remain key drivers of growth in 2016. Poverty rates are expected to fall at a slower rate, with poor households concentrated in rural areas affected by falling agricultural prices. Downside risks to economic growth include a hard landing in China accompanied by global financial turmoil as well as heightened domestic political uncertainty. Nevertheless, ample fiscal and monetary buffers, a sound financial sector and strong fundamentals will help Thailand weather shocks.